The Principles of Screening and Therapy of Snoring and Obstructive Sleep Apnea Syndrome - A. G. Volkov; T. V. Zolotova; L. S. Davydova (Медицинский вестник Юга России, 2012)
Purpose: To identify and assess the leading causal factor in the development of snoring disease for the appointment of an individual special subsequent treatment.Materials and Methods: We examined 86 people who complained of snoring. The portable monitoring (PM) of sleep was held, during which we recorded airflow, breathing and oxygenation of blood. On the basis of the PM was isolated group of patients with simple ronhopathia and mild OSA for further assessment. The electromyography of the soft palate was prescribed, anterior active rhinomanometry, CT of the paranasal sinuses, consulting orthodontist indicated.Results: The cause of uncomplicated snoring and mild OSA in 52.9% cases were anatomical and pathological changes in the nasal cavity and paranasal sinuses, in which case the surgical treatment is effective. Hypotonia of the muscles of the soft palate in conjunction with hypertrophy of the soft palate was the cause of snoring in 23.5% of surveyed.Summary: Treatment of such patients consisted of electrical stimulation of the muscles of the soft palate, or surgical intervention on the soft palate.